Synthesis of interventions using an interRAI tool to guide care management and assess intervention efficacy in older adults: protocol for a scoping review - Katarzyna Szczerbińska; George Heckman; Johanna de Almeida Mello; Emmanuel Bagaragaza; Caitlin McArthur; Ilona Barańska; Nazanin Nasiri; Nick W Bray (BMJ Open, 2025)
Introduction interRAI is a global collaboration of clinicians, researchers and policy-makers who have developed a suite of assessment tools to assess the health status and care needs of older adults in various settings (ie, home, long-term care, etc). We aim to determine how interRAI tools have been used as an intervention and to evaluate intervention efficacy in older adults (65+) across diverse healthcare settings. Importantly, given the deployment of interRAI primarily in high-income countries, we anticipate that the findings may have minimal relevance to low- and middle-income nations, where there is an immediate and urgent need for equity in geriatric assessment.Methods and analysis To be included, all studies must satisfy our inclusion criteria, outlined by the population (ie, older adults and/or individuals providing some element of care to older adults), intervention (ie, randomised or non-randomised), comparator (ie, with or without one) and outcome (ie, how the interRAI formed the basis of a study intervention). Our search strategy is based on previous reviews of interRAI tools, our research and clinical experience, and the expertise of a specialised librarian. In addition to PubMed, we will conduct our search without date or language restrictions in Scopus, Embase,Cumulative Index to Nursing and Allied Health Literature (CINAHL), Academic Search Premier and PsycInfo. Study screening will employ a team-based approach, with Kappa statistics >0.8 indicating ‘substantial’ agreement and an acceptable threshold. Data extraction will capture the study ID and design, as well as sample characteristics and outcomes. Reporting will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews, with findings presented graphically and narratively.Ethics and dissemination Ethics approval is not required. Our knowledge dissemination strategies include traditional research avenues (ie, manuscript publications). We will also create an infographic to disperse widely and leverage existing partnerships to provide community presentations.Registration details https://doi.org/10.17605/OSF.IO/BGJKP